Experimental studies for the cyclability of salt hydrates for thermochemical heat storage. (February 2016) - Donkers, P.A.J.; Pel, L.; Adan, O.C.G.
Abstract : Highlights: CuCl2 is the most promising heat storage material based on used conditions of these cycling tests. The production of pore water may be considered as a good indicator for cyclability. Original grains dehydrate at higher temperatures than grains that dehydrate in subsequent runs. Abstract: Salt hydrates have promising potential as heat storage materials by use of their hydration/dehydration reaction. These hydration/dehydration reactions are studied in this paper for CuCl2, CuSO4, MgCl2 and MgSO4 . During a hydration/dehydration reaction, the salt shrinks and expands as a result of the differences in densities of the phases. As a result, after the first dehydration cycle, the crystal is fractured into a pseudomorphic state that releases the water molecules more easily. The effect of fracturing is larger in case of hydrates with larger volumetric changes. In this study the performance of hydrates during cyclic loading is related to the pore water production and volume variations. On the basis of such data, it is concluded that CuCl2 is the most promising heat storage material.